"Historical Falsification" as a Master Trope in the Official Discourse on History Education in Putin's Russia. Issue 1 (1st March 2021) - Fedor, Julie
Abstract: This article explores a key claim underpinning Russian official memory politics, namely, the notion that Russia's past (and especially the role it played in the Second World War) is the object of a campaign of "historical falsification" aimed at, among other things, undermining Russian sovereignty, especially by distorting young people's historical consciousness. Although "historical falsification" is an important keyword in the Kremlin's discourse, it has received little scholarly attention. Via an analysis of official rhetoric and methodological literature aimed at history teachers, I investigate the ideological functions performed by the concept of "historical falsification." I show how it serves to reinforce a conspiratorial vision of Russia as a nation under siege, while simultaneously justifying the drive toward greater state control over history education.